2010
DOI: 10.1039/b921073c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatinine and specific gravity normalization on urinary biomarker 1,6-hexamethylene diamine

Abstract: Urine amine levels used as biomarkers of diisocyanate exposure have usually been normalized with creatinine concentration. The suitability of using creatinine concentration or specific gravity for these biomarkers in exposure assessment has not been established. We investigated the effect of creatinine concentration and specific gravity on urine 1,6-hexamethylene diamine (HDA) levels in multiple mixed linear regression models using quantitative dermal and inhalation exposure data derived from a survey of autom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Therefore, the use of MEAA for a biomarker of exposure for JP-8 is valid either as concentration in urine with or without the creatinine adjustment. Although other researchers (Gaines et al 2010) have suggested that other urine level normalization schemes are better than creatinine adjustment, the differences in the MEAA levels between exposure workgroup categories are so large that it would not change the statistical significance of this study. Some additional comments about the statistics used in this presentation and its obvious limitations are necessary.…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, the use of MEAA for a biomarker of exposure for JP-8 is valid either as concentration in urine with or without the creatinine adjustment. Although other researchers (Gaines et al 2010) have suggested that other urine level normalization schemes are better than creatinine adjustment, the differences in the MEAA levels between exposure workgroup categories are so large that it would not change the statistical significance of this study. Some additional comments about the statistics used in this presentation and its obvious limitations are necessary.…”
Section: Discussionmentioning
confidence: 81%
“…This was not an unexpected result; the use of creatinine to normalize urinary analyte concentrations has been extensively reported to not necessarily improve correlation of dose to exposure for other urinary components (Allessio et al 1985;Boeniger et al 1993;Carrieri et al 2001). Gaines et al (2010) suggested the use of urine specific gravity for biomarker normalization as an alternative to creatinine. However, for the current JP-8 exposure study, creatinine-adjusted and nonadjusted values were the only normalization schemes investigated.…”
Section: Resultsmentioning
confidence: 90%
“…3 We further concluded that creatinine should be used as an independent variable in exposure modeling to account for the water content in the urine sample collected from a worker exposed to HDI. 3,8 However, in our exposure models relating inhalation and dermal HDI exposure to urine HDA levels, considerable intra- and inter-person variability was observed, 3 which would compromise the use of urine HDA as a biomarker for occupational exposure to HDI. To effectively use individual urine HDA levels in monitoring exposure, evaluating personal protection, and establishing regulatory compliance, determining the cause(s) of the variability is critical.…”
Section: Introductionmentioning
confidence: 94%